Laser propulsion of microsphere in water using tapered fiber-induced shock wave - Yang Ge; Gaoqian Zhou; Xulong Yang; Ying Chen; Xianqi Tang; Hangyang Li (AIP Advances, 2024)
The driving experiment of SiO2 microspheres in a water environment was carried out by using tapered fiber microstructures to transmit short pulse lasers. The fiber microstructure can generate plasma and spherical shock waves to drive SiO2 microspheres. Through theoretical simulation, the propagation characteristics of shock waves and the dynamic characteristics of microspheres were studied. In the experiment, a high-speed COMS camera was used to capture the images of shock wave diffusion and microsphere motion. A linear relationship between the driving behavior of microspheres and the laser energy distribution is observed. The driving behavior of microspheres is attributed to the resultant force caused by spherical shock wave diffusion. We find that the initial driving velocity approximately follows the inverse quadratic function of the radius ratio of the spherical wave, which is consistent with the experimental results. Compared with the traditional technology, this method has the advantages of directional stability, good security, anti-interference, and so on. It can be used for stable directional driving of micron objects in a water environment.